Lignans Extract from Knotwood of Norway Spruce-A Possible New Weapon against GTDs - Špetík, Milan; Balík, Josef; Híc, Pavel; Hakalová, Eliška; Štůsková, Kateřina; Frejlichová, Lucie; Tříska, Jan; Eichmeier, Aleš (Journal of fungi (Basel, Switzerland), 2022)
Grapevine trunk diseases (GTDs) pose a major threat to the wine industry worldwide. Currently, efficient biological methods or chemical compounds are not available for the treatment of infected grapevines. In the present study, we used an extract from the knotwood of spruce trees as a biological control against GTDs. Our in vitro trial was focused on the antifungal effects of the extract against the most common GTD pathogens-Cadophora luteo-olivacea, Dactylonectria torresensis, Diaporthe ampelina, Diaporthe bohemiae, Diplodia seriata, Eutypa lata, and Phaeoacremonium minimum. Our in vitro trial revealed a high antifungal effect of the extract against all tested fungi. The inhibition rates varied among the different species from 30% to 100% using 1 mg·mL-1 extract. Subsequently, the efficiency of the extract was supported by an in planta experiment. Commercial grafts of Vitis vinifera were treated with the extract and planted. The total genomic DNA of grapevines was extracted 10 days and 180 days after the treatment. The fungal microbial diversities of the treated/untreated plants were compared using high-throughput amplicon sequencing (HTAS). Treated plants showed 76.9% lower relative abundance of the genus Diaporthe and 70% lower relative abundance of the genus Phaeoacremonium 10 days after treatment. A similar scenario was observed for the genus Cadophora 180 days after treatment, where treated plants showed 76% lower relative abundance of this genus compared with untreated grapevines.
Keywords: GTD; HMR; grapevine; Norway spruce; bioprotection; 7-hydroxymatairesinol; wood extract